Análisis multitemporal de la superficie ocupada por la plantación de guarango (Caesalpinia spinosa) en la parroquia rural Valparaíso cantón Guano. - Martínez Vera, Nancy Paola (2022)
The objective of this research was to perform a multitemporal analysis of the area occupied by the plantation of “guarango” (Caesalpinia spinosa), in the rural parish of Valparaíso, Guano canton, since this legume has a high conservation value in the recovery of soils that have suffered a process of erosion. The methodology was based on the use and digitization of satellite images of the years 2012, 2016 and 2020. In addition, we worked with the ArcGIS program for the processing of the information mainly in the development of the supervised classification, in order to establish the dynamics of land use by calculating the TCA, to know the percentage that has been modified in the study area. The results obtained for the “guarango” plantation show that in the year 2012 there were no values of this land use class, due to the fact that in those years by bibliographic data it is known that a reforestation process began in Valparaíso. In 2016, a change of 0.6% of the total area of the parish was evidenced, however, in the period 2020 the area occupied by the species decreased with only 0.3% of the total area of the study area; where climatic, edaphic and anthropic factors were the precursors of this decrease. For this reason, a conservation plan for the “guarango” was proposed, due to the benefits provided by this forest species, to protect the soils of the inter-Andean zone of Valparaíso, which have suffered a process of erosion and present fertility problems